SENTIMEN ANALYSIS OF BBM PRICES BASED ON FACEBOOK USER COMMENTS USING THE LEXICON METHOD (CASE STUDY OF THE INDONESIAN VOA PAGE ) - Arofah, Nabialtul; Utomo, Aryo Nur (JURNAL REKAYASA INFORMASI, 2024)
Facebook is a networking site that can be used as a place to give opinions on current issues. One of them is the issue of rising fuel prices in September 2022. Increasing fuel prices has always been a polemic among the people. This study aims to determine the sentiment on the issue using the lexicon method. The lexicon method is a way of classifying sentiment into three classes: negative, positive, and neutral. The results of this study are negative sentiment with a total of 649 lines of data and a percentage of 53.81%, positive sentiment with 344 lines and a percentage of 28.52%, and neutral sentiment with 213 lines and a percentage of 17.7%. Keywords: Facebook, BBM, Anslysis Sentiment, Lexicon